Effects of Marathon Running on Cardiac Markers and Endothelin-1 in EIH Athletes - Kim, Y. J.; Shin, Y. O.; Lee, Y. H.; Jee, H. M.; Shin, K. A.; Goh, C. W.; Kim, C. H.; Min, Y. K.; Yang, H. M.; Lee, J. B. (International Journal of Sports Medicine, 2013)
The aim of the present study was to determine the changes in cardiac makers and endothelin-1 (ET-1) in marathoners with exercise induced hypertension compared to normotensive controls before and after running a marathon. Among a total of 70 volunteers, 10 marathoners with systolic blood pressure (SBP) greater than 210 mmHg during a treadmill exercise stress test were selected as an exercise-induced hypertension group (EIH) and 10 marathoners with normal SBP were selected as a control group (CON). Blood was collected from all volunteers 2 h before and immediately after a marathon: creatinine kinase (CK), CK-MB, cardiac tropoin-I (cTnI), N-terminal pro-brain natriuretic peptide (NT-proBNP), and endothelin-1(ET-1). Cardiac markers, CK, CK-MB, and CK-MB/CK ratio significantly increased in both EIH and CON; significance was not observed between the groups. Significant increases were not observed in high sensitive-C reactive protein (hs-CRP) after the race nor between the groups. Significant increases in cTnI and NT-proBNP were observed after the race in both groups. In addition, EIH showed greater increase than CON after the race. In conclusion, increased vascular tone in EIH during a marathon increased blood pressure and myocardial burden which in turn increased myocardial cell membrane permeability to further increase myocardial tension to the point of cTnI release.
Keywords: hypertension; creatine kinase; cTnI; NT-proBNP